Optimizing yield distribution under biological and economic constraints: Florida strawberries as a model for perishable commodities. (December 2015) - Wu, Feng; Guan, Zhengfei; Whitaker, Vance
Abstract: In this interdisciplinary study we propose a modeling framework for deriving the optimal yield curve for strawberry production in Florida that maximizes the profit of growers given competition from California and Mexico and sensitive price responses to market supply. The model integrates both biological and economic constraints. The biological constraints for Florida production are formulated assuming that potential improvement of yield has genetic and horticultural limits, while economic constraints account for price changes in response to supply. The optimal yield curves derived show clear differences from the historical yield patterns observed in Florida, indicating that yields during the first 6 to 8 weeks of the season should be maximized to realistic limits and that total season yields should be limited to 27, 465 and 32, 415 kg/ha under two different yield distribution scenarios assuming current acreage and market demand. Obtaining optimal yield distributions under the two scenarios could generate 7685 and 14, 293 per ha more profit, whereas the historical yield pattern will result in significant losses under assumed acreage, raising concerns about the sustainability of the industry. The results of this study will be used to guide efforts in breeding and improvement of cultural practices and will assist growers in making informed decisions on cultivars and technologies/practices to adopt to maximize profit. The methodology proposed can be adapted to other regions or countries and used for other perishable crops with extended production seasons. Highlights: We develop a model to derive optimal yield curves for Florida strawberries. The optimal yield curves show clear differences from historical yield patterns. Total yield under optimal distribution scenarios has an upper limit. Obtaining the optimal yield curve could generate 7700–14, 300 more profit per ha. The results raise concerns regarding industry sustainability under current conditions.